A genomic footprint of hybrid zone movement in crested newts. Issue 2 (9th May 2017) - Wielstra, Ben; Burke, Terry; Butlin, Roger K.; Avcı, Aziz; Üzüm, Nazan; Bozkurt, Emin; Olgun, Kurtuluş; Arntzen, Jan W.
Abstract : Speciation typically involves a stage in which species can still exchange genetic material. Interspecific gene flow is facilitated by the hybrid zones that such species establish upon secondary contact. If one member of a hybridizing species pair displaces the other, their hybrid zone would move across the landscape. Although theory predicts that moving hybrid zones quickly stagnate, hybrid zones tracked over one or a few decades do not always follow such a limitation. This suggests that hybrid zones have the potential to traverse considerable distances over extended periods of time. When hybrid zones move, introgression is predicted to result in biased gene flow of selectively neutral alleles, from the receding species into the advancing species. We test for such a genomic footprint of hybrid zone movement in a pair of crested newt species (genus Triturus ) for which we have a priori support for westward hybrid zone movement. We perform a multilocus phylogeographical survey and conduct Bayesian clustering analysis, estimation of ancestry and heterozygosity, and geographical cline analysis. In a 600 km wide area east of the present day hybrid zone a genomic footprint constitutes empirical evidence consistent with westward hybrid zone movement. The crested newt case suggests that hybrid zone movement can occur over an extensive span of time and space. Inferring hybrid zone movement provides fundamental insight into historical biogeography and the speciation process, and we anticipate that hybrid zones will prove to be far more mobile than currently appreciated.